2014
DOI: 10.1242/jcs.158295
|View full text |Cite
|
Sign up to set email alerts
|

Multiple regulatory levels influence cell integrity control by PKC ortholog Pck2 in fission yeast

Abstract: The fission yeast protein kinase C (PKC) ortholog Pck2 controls cell wall synthesis and is a major upstream activator of the cell integrity pathway (CIP) and its core component, the MAP kinase Pmk1 (also known as Spm1), in response to environmental stimuli. We show that in vivo phosphorylation of Pck2 at the conserved T842 activation loop during growth and in response to different stresses is mediated by the phosphoinositide-dependent kinase (PDK) ortholog Ksg1 and an autophosphorylation mechanism. However, T8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 43 publications
1
36
0
3
Order By: Relevance
“…Nevertheless, this complex contributes to de novo Pck2 synthesis, which is essential to activate the CIP in response to cell wall damage or glucose exhaustion, but not to other stimuli like saline stress29. To identify the main components of this novel regulatory mechanism, we analyzed Pck2 levels and Pmk1 activation in a series of mutants lacking upstream regulators or downstream effectors of the TORC2 signaling cascade.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, this complex contributes to de novo Pck2 synthesis, which is essential to activate the CIP in response to cell wall damage or glucose exhaustion, but not to other stimuli like saline stress29. To identify the main components of this novel regulatory mechanism, we analyzed Pck2 levels and Pmk1 activation in a series of mutants lacking upstream regulators or downstream effectors of the TORC2 signaling cascade.…”
Section: Resultsmentioning
confidence: 99%
“…Rho GTPases Rho1 and Rho2 are the main positive regulators of the CIP through Pck2, one of the two orthologs of protein kinase C (PKC) in this organism28. Similar to Gad8 and Psk1, Pck2 activation requires activation loop phosphorylation by Ksg1 (PDK1), and undergoes subsequent autophosphorylation of the turn motif29. These events, together with binding to Rho1 and/or Rho2, stabilize and render Pck2 catalytically competent to modulate cell integrity through activation of Pmk129.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the fission yeast pathway is strongly activated by osmotic stress, whereas heat and cell wall stress lead to a less pronounced activation with slower kinetics (18,20). We have recently shown that delayed Pmk1 activation under cell wall stress or glucose deprivation, but not during osmotic stress, is linked to enhanced Pck2 translation mediated by the TORC2 complex (52). Thus, different activation mechanisms may have evolved to use this conserved response pathway for distinct environmental conditions in different species.…”
Section: Wildtype Pil1mentioning
confidence: 99%